Hardware/Software Co-Design: Principles and Practice - Staunstrup, Jørgen; Wolf, Wayne (Springer US, 1997)
Introduction to Hardware-Software Co-Design presents a number of issues of fundamental importance for the design of integrated hardware software products such as embedded, communication, and multimedia systems. This book is a comprehensive introduction to the fundamentals of hardware/software co-design. Co-design is still a new field but one which has substantially matured over the past few years. This book, written by leading international experts, covers all the major topics including: fundamental issues in co-design; hardware/software co-synthesis algorithms; prototyping and emulation; target architectures; compiler techniques; specification and verification; system-level specification. Special chapters describe in detail several leading-edge co-design systems including Cosyma, LYCOS, and Cosmos. Introduction to Hardware-Software Co-Design contains sufficient material for use by teachers and students in an advanced course of hardware/software co-design. It also contains extensive explanation of the fundamental concepts of the subject and the necessary background to bring practitioners up-to-date on this increasingly important topic
Keywords: Engineering; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design; Electrical Engineering; Software Engineering/Programming and Operating Systems; Software engineering; Computer-aided engineering; Electrical engineering; Electronic circuits; CASHE